Structural Effect of Oil Price Shocks and Food Importation on Economic Growth in Nigeria Using SVAR Model - Sani Abdulrahman Bala; Ali Alhassan (Sekolah Tinggi Ekonomi dan Bisnis Islam Lampung, 2018)
The study empirically examines the effect of oil price shocks and food importation on economic growth in Nigeria along with two control variables i.e. exchange rate and inflation using Structural Vector Autoregressive (SVAR) Model covering the period of 1970 to 2015. The result from SVAR short-run pattern and long-run pattern indicate that GDP has recently been affected by all variables in the model. More also, it indicates a significant permanent effect of crude oil price shocks and food imports on economic growth, while the result further indicates a transitory effect of exchange rate and inflation on economic growth. For significant t-value of the long run SVAR estimate matrix, confirms long effect of crude oil price shocks, food imports, exchange rate and inflation on economic growth in Nigeria. The results from structural response indicate that crude oil have high positive impact on GDP at the initial period and negative impact at the end of the period. Furthermore, food imports have high negative effect on GDP, while GDP response negatively to exchange rate and inflation rate from the period. The result from the structural decompositions indicates that crude oil price and food imports and exchange rate contribute more variability to GDP, while inflation contribute less variability in explaining the variation of GDP in Nigeria. The study recommends that government should come up with a policy that will focus on alternative sources of government revenue by investing more in real sectors especially agriculture in order to withstand vicissitudes of oil shocks in future.